Modified coal gangue coupled perylene bisimide composite material as well as preparation method and application thereof

The modified coal gangue-coupled perylene imide composite material addresses the limitations of traditional photocatalysts by enhancing stability and efficiency through surface modification and coupling, effectively treating organic pollutants and heavy metal ions.

CN119186500AActive Publication Date: 2024-12-27SHAANXI UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411385859.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Traditional photocatalytic materials like TiO2 face challenges such as easy recombination of photogenerated electron-hole pairs and low light utilization rate, while perylene imides have limitations in practical applications due to small specific surface area and insufficient active sites.

Method used

A modified coal gangue-coupled perylene imide composite material is prepared by calcining coal gangue, modifying it with a silane coupling agent to introduce amino groups, and coupling it with perylene diimide to form a stable composite with enhanced photocatalytic performance.

Benefits of technology

The composite material shows improved stability and efficiency in photocatalytic reactions, particularly under visible light irradiation, effectively adsorbing and degrading organic pollutants like Cr(VI), with a simple and cost-effective preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a modified coal gangue coupled perylene bisimide composite material and a preparation method and application thereof, the preparation method comprises the following steps: S1, calcining coal gangue to obtain calcined modified coal gangue; s2, immersing the calcined modified coal gangue into a solution containing a silane coupling agent, and stirring to obtain amino modified coal gangue; s3, adding the amino modified coal gangue into the perylene diimide solution, adding triethylamine, stirring, adding a hydrochloric acid solution, and stirring to obtain the modified coal gangue coupled perylene diimide composite material. According to the modified coal gangue coupled perylene bisimide composite material, the stability and efficiency of perylene bisimide in a photocatalytic reaction are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of environmental engineering and material science, and in particular to a modified coal gangue-coupled perylene imide composite material, a preparation method thereof, and application in the field of photocatalysis. Background Art

[0002] Faced with the increasingly severe water and air pollution problems worldwide, the development of efficient, economical and environmentally friendly pollutant treatment technologies has become a top priority in contemporary scientific research. Photocatalytic technology has attracted much attention due to its ability to degrade organic pollutants using sunlight or artificial light sources at room temperature and pressure. However, although traditional photocatalytic materials such as TiO2 are highly active, their efficiency in practical application scenarios still needs to be improved due to defects such as easy recombination of photogenerated electron-hole pairs and low light utilization rate.

[0003] Perylene imide materials have attracted extensive attention in the field of photocatalysis in recent years due to their unique electronic structure and photochemical stability. This type of material not only has a broad absorption spectrum, but also can effectively separate and transfer photogenerated electron-hole pairs, thereby greatly improving the photocatalytic efficiency. Despite this, perylene imide still faces limitations in practical applications, such as small specific surface area and insufficient active sites. Summary of the invention

[0004] In order to solve the above problems of the prior art, the present invention provides a modified coal gangue-coupled perylene imide composite material and a preparation method and application thereof, which significantly improves the stability and efficiency of perylene imide in photocatalytic reactions.

[0005] The present invention is achieved through the following technical solutions: A method for preparing a modified coal gangue-coupled perylene imide composite material comprises the following steps: S1, calcining the coal gangue to obtain calcined modified coal gangue; S2, immersing the calcined modified coal gangue in a solution containing a silane coupling agent and stirring to obtain amino-modified coal gangue; S3, adding amino-modified coal gangue into the perylene diimide solution, adding triethylamine, stirring, adding hydrochloric acid solution, stirring, and obtaining a modified coal gangue-coupled perylene diimide composite material.

[0006] Preferably, in S1, the calcination temperature is 500-700° C., and the calcination time is 3-4 hours.

[0007] Preferably, S1 specifically comprises: calcining the coal gangue, then immersing it in 2-4 M hydrochloric acid for 20-24 hours, and washing it to obtain calcined modified coal gangue.

[0008] Preferably, in S1, the coal gangue is obtained by the following method: crushing the coal gangue, passing it through a 200-400 mesh sieve, and washing it with water for multiple times.

[0009] Preferably, S2 specifically comprises: immersing the calcined modified coal gangue in a solution containing 2% to 4% of a silane coupling agent, stirring at room temperature for 24 to 48 hours, washing with water and drying.

[0010] Preferably, in S2, the silane coupling agent is one of 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-aminopropyltriisopropoxysilane and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.

[0011] Preferably, in S3, the perylene diimide solution is obtained by the following method: under the protection of inert gas, perylene-3,4,9,10-tetracarboxylic dianhydride, aminopropionic acid and imidazole are mixed, and heated at 100-110°C for 4-5h; the reaction mixture is cooled to room temperature and then dispersed in anhydrous ethanol and hydrochloric acid solution, the solid is filtered and collected, and the obtained solid is fixed, dried and dissolved in water.

[0012] Preferably, in S3, the ratio of amino-modified coal gangue, perylene diimide and triethylamine is (2-5) g: (1-4) g: (336-834) μL.

[0013] The present invention provides a modified coal gangue coupled perylene imide composite material obtained by the above-mentioned preparation method.

[0014] The present invention provides application of the modified coal gangue coupled perylene imide composite material in adsorption / photocatalytic synergistic treatment of organic pollutants or heavy metal ions.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention calcines coal gangue (CG) to activate the surface of the coal gangue, and then uses a silane coupling agent to modify the surface of the activated coal gangue, introduces amino functional groups, and enhances its interaction ability with organic molecules; then the modified coal gangue is used as a carrier and perylene diimide is coupled to form a composite material with excellent adsorption photocatalytic performance. The rich silicate components inside the coal gangue can form a stable chemical bond with perylene diimide through a silane coupling agent, thereby improving the stability of the composite material and enhancing the photocatalytic efficiency. The present invention utilizes the natural structure of coal gangue and the surface modification function of the silane coupling agent to significantly improve the stability and efficiency of perylene diimide in the photocatalytic reaction. The composite material shows significant photocatalytic activity under visible light irradiation, and is particularly suitable for adsorption and degradation of Cr (VI). Among them, the triethylamine used is an organic base, which mainly plays the role of adjusting pH and promoting dissolution in the reaction. When amino-modified gangue is added to the PDI solution, triethylamine can prevent excessive acidity from affecting the reactivity of the amino group by neutralizing the acidic protons in the system, and maintain a suitable pH value in the solution to promote the effective combination between PDI and amino-modified gangue. In addition, the presence of triethylamine helps to enhance the interaction between the amino group and the carboxyl group or other functional groups in PDI, thereby promoting the formation of a more stable composite structure. Adding hydrochloric acid is to induce the formation of a supramolecular nanostructure of PDI. Since triethylamine is a base, adding hydrochloric acid can quickly reduce the pH of the solution, so that PDI is protonated, thereby promoting its intermolecular self-assembly to form a stable supramolecular nanostructure. In addition, the addition of hydrochloric acid can also help precipitate the product, so that the combination of PDI and amino-modified gangue is tighter. The preparation process of the material of the present invention is simple, low cost, and has potential industrial application prospects. Through the present invention, not only can the abandoned gangue resources be effectively utilized, but also a kind of environmentally friendly and efficient photocatalytic material can be provided, which provides a new technical solution for treating environmental pollution problems.

[0016] Furthermore, after calcining the gangue, it is subjected to acid washing to remove metal impurities and some unstable components on the surface of the mineral.

[0017] Furthermore, the gangue is screened and pickled to ensure the consistency of particle size and remove dust and soluble impurities on the surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1XRD patterns of the products prepared in Examples 1-3; (a) XRD patterns of calcined modified coal gangue and amino-modified coal gangue; (b) XRD pattern of modified coal gangue coupled with perylene imide composite material.

[0020] Figure 2 Infrared spectra of the products prepared in Examples 1-3; (a) infrared spectrum of calcined modified coal gangue; (b) infrared spectrum of amino-modified coal gangue; (c) infrared spectrum of modified coal gangue coupled with perylene imide composite material.

[0021] Figure 3 SEM images of the products prepared in Examples 1-3; (a), (b), (c) are unmodified coal gangue; (d), (e), (f) are calcined modified coal gangue; (g), (h), (i) are amino-modified coal gangue; (j), (k), (l) are modified coal gangue coupled with perylene imide composite materials.

[0022] Figure 4 The adsorption photocatalytic synergistic performance diagram of each product prepared in Examples 1-3; (a) is the removal effect of MCG-500, MCG-600, MCG-700, NMCG-500, NMCG-600, and NMCG-700 on Cr (VI); (b) is the removal effect of modified coal gangue coupled perylene imide composite material on Cr (VI). (c) is the kinetic fitting curve of MCG-500, MCG-600, MCG-700, NMCG-500, NMCG-600, and NMCG-700; (d) is the kinetic fitting curve of modified coal gangue coupled perylene imide composite material.

[0023] Figure 5 This is a graph showing the adsorption photocatalytic cyclic performance of the modified gangue-coupled perylene imide composite material prepared in Example 1-3. DETAILED DESCRIPTION

[0024] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0025] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0026] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0027] The method for preparing the modified gangue-coupled perylene imide composite material of the present invention comprises the following steps: S1, calcining the coal gangue to obtain calcined modified coal gangue; S2, immersing the calcined modified coal gangue in a solution containing a silane coupling agent and stirring to obtain amino-modified coal gangue; S3, adding amino-modified coal gangue into the perylene diimide solution, adding triethylamine, stirring, adding hydrochloric acid solution, stirring, and obtaining a modified coal gangue-coupled perylene diimide composite material.

[0028] In the present invention, S1 specifically comprises: calcining the gangue at 500-700°C for 3-4 h for activation treatment, and then immersing the gangue in 2-4 M hydrochloric acid for 20-24 h to remove metal impurities and some unstable components on the surface of the mineral, and then washing with deionized water until the pH value is neutral.

[0029] The present invention further includes a pretreatment step of the coal gangue before S1: the coal gangue is crushed to 200-400 meshes, washed with deionized water for multiple times to remove dust and soluble impurities on the surface, and screened to ensure the consistency of particle size.

[0030] In the present invention, S2 is specifically: immersing the coal gangue in a solution containing a silane coupling agent, the concentration of the silane coupling agent is about 2% to 4%; stirring at room temperature for 24 to 48 hours to allow the silane coupling agent molecules to react with the hydroxyl groups on the surface of the coal gangue to form stable chemical bonds, and then washing with deionized water and drying to obtain amino-modified coal gangue.

[0031] The silane coupling agent of the present invention is one of 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-aminopropyltriisopropoxysilane and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.

[0032] In the present invention, S3 is specifically: slowly adding amino-modified coal gangue to a perylene diimide solution, adding triethylamine, stirring, and then adding HCl solution to form a PDI supramolecular nanostructure, washing with distilled water and anhydrous ethanol by alternating centrifugation until the pH value of the washing liquid becomes neutral, collecting and drying the solid, and grinding it into powder for storage.

[0033] In the present invention, the ratio of amino-modified coal gangue, perylene diimide and triethylamine is (2-5) g: (1-4) g: (336-834) μL.

[0034] The preparation method of the perylene diimide solution is as follows: first, perylene-3,4,9,10-tetracarboxylic dianhydride, aminopropionic acid and imidazole are heated at 100-110° C. under an inert gas for 4-5 h; the reaction mixture is cooled to room temperature and dispersed in anhydrous ethanol and HCl solution; the obtained red solid is collected by filtering through a 0.22 μm membrane filter, the collected solid is dried at 60-70° C., and then dissolved in .

[0035] The ratio of perylene-3,4,9,10-tetracarboxylic dianhydride, aminopropionic acid and imidazole is 3.5 mmol:28.0 mmol:18 g. The ratio of anhydrous ethanol and HCl solution is V (eth) :V (HCI) =1:3.

[0036] The modified gangue-coupled perylene imide composite material prepared by the present invention can adsorb / photocatalytically synergistically treat organic pollutants or heavy metal ions. The composite material is used for at least one specific photocatalytic reaction, including but not limited to photocatalytic decomposition of water to produce hydrogen, photocatalytic degradation of dyes, photocatalytic degradation of organic pollutants or photocatalytic CO2 reduction.

[0037] Example 1 (1) The gangue was crushed to 400 mesh and washed with deionized water several times to remove dust and soluble impurities on the surface. Three portions of washed gangue were prepared and calcined at 500 °C in a muffle furnace for 3 h for activation. The gangue was then immersed in 4 M hydrochloric acid for 20 h to remove metal impurities and some unstable components on the surface of the gangue, and then washed with deionized water until the pH value was neutral to obtain calcined modified gangue (MCG), which was recorded as MCG-500.

[0038] (2) Silane coupling agent treatment The modified coal gangue obtained after pretreatment was immersed in a solution containing 3-aminopropyltriethoxysilane with a concentration of about 2% and stirred at room temperature for 24 h to allow the coupling agent molecules to react with the hydroxyl groups on the surface of the coal gangue to form stable chemical bonds. The mixture was then washed with deionized water and dried to obtain amino-modified coal gangue (NMCG), which was recorded as NMCG-500.

[0039] (3) Preparation of coal gangue-coupled perylene imide composite photocatalytic materials First, 3.5 mmol perylene-3,4,9,10-tetracarboxylic dianhydride, 28.0 mmol aminopropionic acid and 18 g imidazole were heated at 100°C in an inert atmosphere for 4 h. The reaction mixture was cooled to room temperature and dispersed in 100 mL of anhydrous ethanol and 300 mL of 2.0 mol / L HCl. The resulting red solid was collected by filtration through a 0.22 μm membrane filter. The collected solid was dried at 60°C and dissolved in deionized water to prepare 200 mL of perylene diimide (PDI) solution. 2 g NMCG was slowly added to the PDI solution, 834 μL triethylamine was added, stirred for 1 h, and then 27.3 mL 4.0 mol / L HCl was added and stirred for 12 h to form a PDI supramolecular nanostructure. The solution was washed by alternating centrifugation with distilled water and anhydrous ethanol until the pH value of the washing liquid became neutral. The collected solid was completely dried at 60 °C and ground into powder for storage to obtain a modified coal gangue coupled perylene imide composite material (PNMCG), recorded as PMNCG-500.

[0040] Example 2 The method is basically the same as Example 1, except that the calcination temperature in step (1) is 600° C., and MCG-600, NMCG-600, and PNMCG-600 are obtained in step (1), step (2), and step (3), respectively.

[0041] Example 3 The method is basically the same as Example 1, except that the calcination temperature in step (1) is 700° C., and MCG-700, NMCG-700, and PNMCG-700 are obtained in step (1), step (2), and step (3), respectively.

[0042] Example 4 (1) The gangue was crushed to 200 mesh and washed with deionized water several times to remove dust and soluble impurities on the surface. Three portions of washed gangue were prepared and calcined at 700 °C in a muffle furnace for 3 h for activation. The gangue was then immersed in 2 M hydrochloric acid for 24 h to remove metal impurities and some unstable components on the mineral surface, and then washed with deionized water until the pH value was neutral.

[0043] (2) Silane coupling agent treatment The pretreated coal gangue was immersed in a solution containing 3-(2-aminoethyl)aminopropyltrimethoxysilane at a concentration of about 4%. The solution was stirred at room temperature for 48 h to allow the coupling agent molecules to react with the hydroxyl groups on the surface of the coal gangue to form a stable chemical bond. The solution was then washed with deionized water and dried to obtain amino-modified coal gangue (NMCG).

[0044] (3) Preparation of coal gangue-coupled perylene imide composite photocatalytic materials First, 3.5 mmol perylene-3,4,9,10-tetracarboxylic dianhydride, 28.0 mmol aminopropionic acid and 18 g imidazole were heated at 110℃ in an inert gas for 4 h. The reaction mixture was cooled to room temperature and dispersed in 100 mL anhydrous ethanol and 300 mL 2.0 mol / L HCl. The resulting red solid was collected by filtration through a 0.22 μm membrane filter, dried at 70℃ and dissolved in deionized water to prepare 200 mL perylene diimide (PDI) solution. 5 g amino-modified coal gangue was slowly added to the PDI solution, 336 μL triethylamine was added, stirred for 1 h, and then 27.3 mL 4.0 mol / L HCl was added to form PDI supramolecular nanostructures. The mixture was washed alternately by centrifugation with distilled water and anhydrous ethanol until the pH value of the washing solution became neutral. The collected solid was completely dried at 70° C., ground into powder and stored, to obtain a modified coal gangue-coupled perylene imide composite material.

[0045] Figure 1 The XRD diagrams of the products prepared in Examples 1-3 show the XRD diffraction peak characteristics of different samples. It can be seen that the increase in temperature may lead to changes in the crystal phase or rearrangement of the lattice structure. Figure 1 (a) It can be seen that for the calcined modified gangue series samples, with the increase of calcination temperature, the intensity and clarity of some diffraction peaks are enhanced, indicating that the order of the crystal structure increases with the increase of temperature. Sharper and better crystal diffraction peaks were observed for the calcined modified gangue (MCG-600) calcined at a higher temperature of 600°, which may indicate the improvement of grain growth and purity of the crystalline phase. In contrast, the amino modified gangue (NMCG) series samples show different diffraction patterns from the modified gangue series ( Figure 1 (a)). Amino modification introduces new functional groups, such as the diffraction peaks shown in the NMCG-500, NMCG-600 and NMCG-700 samples. Compared with the MCG series samples, the crystallinity of their XRD diffraction peaks is significantly enhanced. These changes may be due to the rearrangement of the crystal structure or possible phase transition caused by the introduction of amino groups. Figure 1(b) XRD patterns of modified gangue-coupled perylene imide composites PNNCG-500, PNNCG-600 and PNNCG-700 obtained at different temperatures (500°C, 600°C, 700°C), which show an obvious sharp peak at about 27°, which may be related to the specific crystal phase of PDI or the interaction with NMCG. The appearance of more sharp peaks in the 2θ range of 20°~30° indicates that with the increase of temperature, a new crystal phase may be formed or the crystal structure is more ordered. The results show that the composite material of NMCG and PDI was successfully prepared.

[0046] Figure 2 The infrared spectra of the products prepared in Examples 1 to 3 are shown in Figure 1. MCG-500, MCG-600, and MCG-700 have a wave number of 3500 cm -1 There is a broad absorption peak near 1000-1100 cm, which may be caused by the stretching vibration of the OH bond, indicating the presence of water or hydroxyl groups. -1 The sharp peaks in the range may indicate the presence of silicon-oxygen bonds (Si-O), which is a common component in coal gangue. As the temperature increases, the intensity of some peaks decreases, which may be due to the removal or transformation of some functional groups caused by heat treatment. Compared with the MCG series, amino modification of NMCG-500, NMCG-600, and NMCG-700 may lead to some new absorption peaks, especially at 1500-1600 cm -1 range, which may be related to the vibration of amino (NH) groups; 3500 cm ⁻1 The broad peak near 1500-1600 cm-1 persists, indicating that even after amino modification, water or hydroxyl groups are still retained. For PNNCG-500, PNNCG-600, and PNNCG-700, the peaks at wavenumbers 1500-1600 cm-1 are -1 The absorption peaks between the two are more significant, which may be related to the C=O vibration in the PDI structure. The changes in other peak positions may reflect the interaction between PDI and NMCG, especially the possible chemical bond formation or structural changes caused by the interaction. These data further prove that the NMCG and PDI composite material was successfully prepared.

[0047] Figure 3 The following are SEM images of the products prepared in Examples 1-3. Figure 3 It is clearly shown in (a), (b), and (c) that the unmodified gangue particles aggregate together to form dense clusters. The surface morphology is rough and irregular, and there is obvious particle aggregation. Figure 3(d), (e), and (f) show the SEM of MCG-600 calcined at 600°C. The calcined coal gangue is more porous than the unmodified CG, and the density is significantly reduced. The particle aggregation phenomenon is significantly reduced, and the material presents a more open and loose structure. Figure 3 (g), (h), and (i) show the SEM images of NMCG-600 calcined at 600 ° C. It can be seen that amino modification further changes the morphology of coal gangue. The particles show a more distinct and separated structure, and the surface roughness and porosity increase. This indicates that amino modification enhances the dispersion of the particles and forms a more uniform and extended morphology. Figure 3 (j), (k), and (l) show SEM images of a large amount of nanofiber PDI loaded on the surface of NMCG-600. It can be clearly seen that PDI forms an obvious covering on the surface of NMCG-600, making the particle surface more complex and rich. The surface morphology of NMCG-600 after loading with PDI is further changed, and the pore structure is more significant, which helps to improve its performance in catalytic and adsorption applications. The results show that calcination modification and amino modification significantly improve the structure and morphology of coal gangue, while the loading of PDI further enhances its surface characteristics and pore structure. These morphological changes are crucial to improving the performance of materials in applications such as catalysis and adsorption.

[0048] The adsorption performance of different gangue samples was tested: 30 mg of different gangue materials were weighed into a 50 mL test tube, 30 mL of 20 mg / L Cr (VI) simulated wastewater solution was added, the test tubes were numbered, and placed in a photochemical reactor at room temperature and 180 rpm for 180 min. The sampling time points were set to 0, 20, 40, 60, 80, 100, 120, 140, 160, 180, 200 and 220 min, respectively. The adsorption was carried out in a dark environment without light before 120 min to achieve adsorption and desorption equilibrium. After 120 min, the xenon lamp was turned on to provide lighting conditions. After each sampling, the suspension sample was placed in a centrifuge tube, centrifuged at 12000 rpm for 3 min, and the supernatant was filtered with a 0.22 μm filter membrane. The Cr (VI) concentration in the filtrate was calculated using the adsorption capacity and removal efficiency by formulas (1) and (2): (1) (2) Among them, q t is the adsorption amount at time t, mg / g; C0 and C t are the initial concentration of the dye and the dye concentration at time t, respectively, in mg / L; V is the volume of the dye solution to be adsorbed, in mL; and m is the amount of adsorbent material added, in g.

[0049] Figure 4 This is a diagram of the adsorption photocatalytic synergistic performance of each product prepared in Examples 1 to 3. Figure 4 (a) shows the removal effect of MCG-500, MCG-600, MCG-700, NMCG-500, NMCG-600 and NMCG-700 on Cr (VI). Under dim light within 120 minutes, the adsorption efficiencies of MCG-500, MCG-600, MCG-700, NMCG-500, NMCG-600 and NMCG-700 were 21.4%, 30.7%, 25.2%, 28.6%, 42.6% and 35.6%, respectively. The adsorption performance reached equilibrium between 80 and 120 min. When the illumination started at 120 min, the photocatalytic efficiencies of MCG-500, MCG-600, MCG-700, NMCG-500, NMCG-600, and NMCG-700 were 29.3%, 49.1%, 43.5%, 47.1%, 67.7%, and 57.1%, respectively. The adsorption efficiency was significantly improved under illumination, indicating that photocatalysis significantly promoted the adsorption. The above conclusions show that MCG-600 has the best adsorption / photocatalytic performance in the calcined modified coal gangue series, while the amino-modified samples generally have better performance than the calcined modified coal gangue, among which the adsorption efficiency of NMCG-600 increased to 42.6%. As shown in Figure (b), among the three groups of NMCG samples loaded with PDI, PNCG-600 has the highest adsorption efficiency, reaching 58.3%, showing the best adsorption performance among all samples. When the illumination started at 120 min, the photocatalytic efficiency reached 78.9% within 100 min. The above conclusions show that the introduction of amino groups not only enhances the adsorption capacity of the composite material for Cr (VI), but also promotes the transfer of electrons from PDI to Cr (VI) through the electron donor function, thereby improving the reduction rate and overall removal efficiency of Cr (VI). Figure 4 (c) and (d) are the pseudo-first-order kinetic fitting curves of the photocatalytic performance of different samples, respectively. The figure shows the photocatalytic rate of different samples. The kinetic results further verify that the photocatalytic activity of calcined modified coal gangue is enhanced after amino modification, and the photocatalytic activity is further enhanced after loading PDI. PNMCG-600 has the largest kinetic constant among all samples (𝑘=1.72×10 −3 ), the coefficient of determination 𝑅 2 =0.991, indicating that it has the fastest removal rate and highest efficiency for Cr(VI). In addition, NMCG-600 and NMCG-700 also showed higher kinetic constants and removal efficiencies, reinforcing the role of amino modification in improving photocatalytic activity.

[0050] Figure 5The performance diagram of the adsorption photocatalytic cycle of the modified gangue-coupled perylene imide composite material prepared in Examples 1 to 3. In the five cycles, the treatment efficiency fluctuated slightly, among which PMCG-600 showed a higher treatment efficiency and excellent stability. The efficiency of the first cycle was 78.9%, and then the efficiency decreased slightly in the five cycles, but remained at a high level as a whole, 78.4% for the second time, 78.2% for the third time, 75.4% for the fourth time, and 70.4% for the fifth time. This shows that although the performance of PMNCG-600 has declined during repeated use, the decline is small and maintains good stability. The performance of PMNCG-500 and PMNCG-700 fluctuates greatly, especially PMNCG-700, whose performance is significantly attenuated during repeated use, which may be related to the loss of material structure or active sites during use. During continuous use, organic matter or other pollutants may accumulate on the catalyst surface, leading to blockage of active sites, reducing the effective surface area, and thus reducing the sites available for adsorption and catalysis.

Claims

1. A method for preparing a modified coal gangue-coupled perylene imide composite material, characterized in that: The following steps are involved: S1, calcining the coal gangue to obtain calcined modified coal gangue; S2, immersing the calcined modified coal gangue in a solution containing a silane coupling agent and stirring to obtain amino-modified coal gangue; S3, adding amino-modified coal gangue into the perylene diimide solution, adding triethylamine, stirring, adding hydrochloric acid solution, stirring, and obtaining a modified coal gangue-coupled perylene diimide composite material.

2. The method for preparing the modified coal gangue-coupled perylene imide composite material according to claim 1, characterized in that: In S1, the calcination temperature is 500~700℃, and the calcination time is 3~4h.

3. The method for preparing the modified coal gangue-coupled perylene imide composite material according to claim 1, characterized in that: S1 specifically comprises: calcining the coal gangue, then immersing it in 2-4 M hydrochloric acid for 20-24 hours, and washing it to obtain calcined modified coal gangue.

4. The method for preparing the modified coal gangue-coupled perylene imide composite material according to claim 1, characterized in that: In S1, the coal gangue is obtained by the following method: the coal gangue is crushed, passed through a 200-400 mesh sieve, and washed with water for multiple times.

5. The method for preparing the modified coal gangue-coupled perylene imide composite material according to claim 1, characterized in that: S2 is specifically as follows: immersing the calcined modified coal gangue in a solution containing 2% to 4% of a silane coupling agent, stirring at room temperature for 24 to 48 hours, washing with water and drying.

6. The method for preparing the modified coal gangue-coupled perylene imide composite material according to claim 1, characterized in that: In S2, the silane coupling agent is one of 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-aminopropyltriisopropoxysilane and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.

7. The method for preparing the modified coal gangue-coupled perylene imide composite material according to claim 1, characterized in that: In S3, the perylene diimide solution is obtained by the following method: under the protection of inert gas, perylene-3,4,9,10-tetracarboxylic dianhydride, aminopropionic acid and imidazole are mixed and heated at 100-110°C for 4-5 hours; the reaction mixture is cooled to room temperature and then dispersed in anhydrous ethanol and hydrochloric acid solution, the solid is filtered and collected, and the obtained solid is fixed, dried and dissolved in water.

8. The method for preparing the modified coal gangue-coupled perylene imide composite material according to claim 1, characterized in that: In S3, the ratio of amino-modified coal gangue, perylene diimide, and triethylamine is (2~5) g: (1~4) g: (336~834) μL.

9. A modified coal gangue-coupled perylene imide composite material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the modified coal gangue coupled perylene imide composite material according to claim 9 in adsorption / photocatalytic synergistic treatment of organic pollutants or heavy metal ions.

Citation Information

Patent Citations

  • Perylenebisimide and composite photocatalytic material thereof, preparation method and application of perylenebisimide and composite photocatalytic material in removal of organic pollutants in water body

    CN111001439A

  • Polyaniline / perylene bisimide organic heterojunction photocatalyst and preparation method and application thereof

    CN111495426A

  • Preparation method and application of flexible composite catalytic membrane

    CN112275321A

  • Catalytic and adsorption material prepared from deep-sea clay and method

    CN113797890A

  • Modified coal gangue adsorbent as well as preparation method and application thereof

    CN115646455A